2008
DOI: 10.6028/jres.113.020
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of 68Ge/68Ga Using Three Liquid Scintillation Counting Based Methods

Abstract: A solution containing 68Ge in equilibrium with its daughter, 68Ga, has been standardized for the first time at the National Institute of Standards and Technology (NIST) using 3 liquid scintillation-based techniques: live-timed 4πβ -γ anticoincidence (LTAC) counting, the Triple-to-Double Coincidence Ratio (TDCR) method, and 3H-standard efficiency tracing with the CIEMAT1/NIST (CNET) method. The LTAC technique is much less dependent on level scheme data and model-dependent parameters and was thus able to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The ratio of calculated doses deposited in the ionization chamber gas for the solid mock syringe to the solutionfilled mock syringe was 0.995 (4) and is consistent with the results given in our previous work (3).…”
Section: Discussionsupporting
confidence: 90%
“…The ratio of calculated doses deposited in the ionization chamber gas for the solid mock syringe to the solutionfilled mock syringe was 0.995 (4) and is consistent with the results given in our previous work (3).…”
Section: Discussionsupporting
confidence: 90%
“…The solutions, and derivatives thereof, were calibrated for radioactivity content at NIST by either primary or secondary methods, as described in Zimmerman et al (5). All dilutions were performed using a carrier solution containing nominally 45 mg each of nonradioactive GeCl 4 and GaCl 3 per gram of solution in 0.5 M HCl.…”
Section: Calibration Of 68 Ge Mock Syringe Sourcesmentioning
confidence: 99%
“…As a potential solution, NIST recently developed a primary standard for the relatively long-lived (half-life, 270.95(16) d) radionuclide 68 Ge in equilibrium with its positron-emitting decay daughter, 68 Ga (5), for the first time. Although the decay properties of 68 Ga are not identical to those of 18 F, there are enough similarities that it has been suggested that 68 Ge/ 68 Ga could be used as a reasonable surrogate, assuming that the necessary correction factors can be determined.…”
mentioning
confidence: 99%
“…All the latter give X-rays between 4 and 8 keV. [1,2]. 68 Ge has a 288 days half-life and disintegrates by 100% electron capture (E.C.)…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the 10 InterDigit bolometers [3] in operation in the Underground Laboratory of Modane (LSM) during the last WIMP search of the Edelweiss-II experiment [4]. They are all 400 g germanium crystals, but two different geometries are present : a cylindrical one (corresponding to half the bolometers, denoted ID40X with X ∈ [1,5]) and a geometry with bevelled edges (also corresponding to half the bolometers, denoted IDX with X ∈ [2, 6]). A more complete description of the detectors is given in Ref.…”
Section: Introductionmentioning
confidence: 99%